2016
DOI: 10.1016/j.ajic.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Copper alloy surfaces sustain terminal cleaning levels in a rural hospital

Abstract: Copper alloys can significantly decrease the burden harbored on high-touch surfaces, and thus warrant inclusion in an integrated infection control strategy for rural hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Multiple infection control bundles have shown that infection control risk mitigation strategies integrating hand hygiene with room cleaning can be effective, but to date only solid copper surfaces have been successfully deployed to consistently demonstrate an ability to minimize the microbial burden found in the built clinical environment. [5][6][7][8] The agent evaluated here, Disinfectant 1, represents a first-of-its-kind disinfectant that offers an ability to debulk the built environment of microbes while addressing the limitations inherent to using EPA-registered disinfectants for daily cleaning-namely, rebound of the biofilm affiliated with surfaces or the introduction of new bioburden secondary to care and housing of patients. The finding that Disinfectant 1 was able to significantly control bioburden on bed rails, a critical touch surface, for up to 24 hours during active patient care warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple infection control bundles have shown that infection control risk mitigation strategies integrating hand hygiene with room cleaning can be effective, but to date only solid copper surfaces have been successfully deployed to consistently demonstrate an ability to minimize the microbial burden found in the built clinical environment. [5][6][7][8] The agent evaluated here, Disinfectant 1, represents a first-of-its-kind disinfectant that offers an ability to debulk the built environment of microbes while addressing the limitations inherent to using EPA-registered disinfectants for daily cleaning-namely, rebound of the biofilm affiliated with surfaces or the introduction of new bioburden secondary to care and housing of patients. The finding that Disinfectant 1 was able to significantly control bioburden on bed rails, a critical touch surface, for up to 24 hours during active patient care warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that U.S. Environmental Protection Agency-registered copper alloys are able to reduce bacterial burdens by 94%, confirming previous observations on the antimicrobial properties of copper. 18,31,32 Assessing the bacterial burden on equipment surfaces allows athletic centers to determine which pieces of equipment afford more attention in hygiene maintenance. Across all sampled equipment, the average concentration of bacteria recovered from surfaces was highest for control dumbbells, with a mean concentration of 10,360 CFU/100 cm 2 ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of copper alloys on high-touch surfaces in the hospital resulted in decreased bacterial counts on surfaces in comparison with control surfaces. [18][19][20][21][22][23] Souli et al found copper coating reduced bacterial burden associated high-touch hospital items and lowered the number of surfaces contaminated with multidrug-resistant bacteria. 24 The ability of copper to lessen bacterial loads rapidly is important for continuously touched surfaces and therefore can more readily reduce the transmission of antibioticresistant bacteria.…”
mentioning
confidence: 99%
“…Another clinical trial in the United States was conducted in the medical-surgical suite in a small rural hospital (18). Six of the 13 single rooms were converted to copper, as were three of the five double rooms.…”
Section: Clinical Resultsmicrobial Reductionmentioning
confidence: 99%